2018
DOI: 10.1038/s41438-018-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of heat stress resistance of cucumber leaves when grafted onto Momordica rootstock

Abstract: Various biotic and abiotic stresses threaten the cultivation of future agricultural crops. Among these stresses, heat stress is a major abiotic stress that substantially reduces agricultural productivity. Many strategies to enhance heat stress tolerance of crops have been developed, among which is grafting. Here, we show that Momordica-grafted cucumber scions have intrinsically enhanced chlorophyll content, leaf area, and net photosynthetic rate under heat stress compared to plants grafted onto cucumber rootst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…In 2016, gross production value is 40,229 million US$ (FAO). However, cucumber is high sensitive to low/high temperature, drought/waterlogging and salt stresses that cause significant reductions in yields (Liu et al 2013Ma et al 2018;Xu et al 2017Xu et al , 2018. In addition, a wide range of soilborne diseases (pathogenes), viruses and nematodes are one of the main constraints on cucumber production (Li and Chen 2017;Liang et al 2019;Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, gross production value is 40,229 million US$ (FAO). However, cucumber is high sensitive to low/high temperature, drought/waterlogging and salt stresses that cause significant reductions in yields (Liu et al 2013Ma et al 2018;Xu et al 2017Xu et al , 2018. In addition, a wide range of soilborne diseases (pathogenes), viruses and nematodes are one of the main constraints on cucumber production (Li and Chen 2017;Liang et al 2019;Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a wide range of soilborne diseases (pathogenes), viruses and nematodes are one of the main constraints on cucumber production (Li and Chen 2017;Liang et al 2019;Liu et al 2017). Although grafting of cucumber plants onto cucurbitaceous rootstocks is an efficiency way to improve abiotic/biotic stress, this technique is labor-intensive (Xu et al 2018). Genetic engineering is a powerful and high efficient way to improve cucumber abiotic/biotic stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…6B), suggesting that HT was subjected to minor damage from ROS. It has also been suggested that the up-regulation of antioxidant enzymes can regulate the ROS level and protect the plant cells from oxidative damage when they are under heat stress [13,20,38,39]. In the present study, some antioxidant enzymes were identi ed, including GST, POD, SOD, APX, and CAT (Fig.…”
Section: Daps Involved In Stress Defensementioning
confidence: 52%
“…In horticultural plants, different rootstocks can induce significant changes in physiological responses (Ren et al, 2018), photosynthesis (Xu et al, 2018), hormonal responses (Ren et al, 2018), environmental adaptation (Yu et al, 2017;Xu et al, 2018), and the sugars and aromatic flavors of the plants (Zhao et al, 2018). Extensive mRNA signaling networks have been reported in the model plants A. thaliana (Thieme et al, 2015) and N. benthamiana (Zhang W. et al, 2014) by bioinformatics and "omics" analyses.…”
Section: "Omics" Analyses Of Macromolecule Signal Exchanges Induced Bmentioning
confidence: 99%
“…Proteomics can be used to analyze the major categories of proteins in different treatments to investigate the mechanisms of graft-enhanced stress tolerance in scions. For example, comparative proteomic analysis was used to show that cucumber scions grafted to Momordica rootstocks could respond to heat stress by differentially accumulating photosynthesis-related proteins (Xu et al, 2018). Therefore, "omics" analyses are important techniques that can be used to unravel the differential accumulation and transport of macromolecular signals in grafted vegetables.…”
Section: "Omics" Analyses Of Macromolecule Signal Exchanges Induced Bmentioning
confidence: 99%